Spatiotemporal consistency of local neural activities: A new imaging measure for functional MRI data - Dong, Li; Luo, C.; Cao, W.; Zhang, R.; Gong, J.; Gong, D.; Yao, D. (John Wiley & Sons, Inc., 2015)
© 2014 Wiley Periodicals, Inc. Purpose To characterize the local consistency by integrating temporal and spatial information in the local region using functional magnetic resonance imaging (fMRI). Materials and Methods One simulation was implemented to explain the definition of FOur-dimensional (spatiotemporal) Consistency of local neural Activities (FOCA). Then three experiments included resting state data (33 subjects), resting state reproducibility data (16 subjects), and event state data (motor execution task, 26 subjects) were designed. Finally, FOCA were respectively analyzed using statistical analysis methods, such as one-sample t-test and paired t-test, etc. Results During resting state (Experiment 1), the FOCA values (P < 0.05, family-wise error [FWE] corrected, voxel size > 621 mm < sup > 3 < /sup > ) were found to be distinct at the bilateral inferior frontal gyrus, middle frontal gyrus, angular gyrus, and precuneus/cuneus. In Experiment 2 (reproducibility), a high degree of consistency within subjects (correlation ˜0.8) and between subjects (correlation ˜0.6) of FOCA were obtained. Comparing event with resting state in Experiment 3, enhanced FOCA (P < 0.05, FWE-corrected, voxel size > 621 mm < sup > 3 < /sup > ) was observed mainly in the precentral gyrus and lingual gyrus. Conclusion These findings suggest that FOCA has the potential to provide further information that will help to better understand brain function in neural imaging. J. Magn. Reson. Imaging 2015;42:729-736.